Life against death : the psychoanalytical meaning of history - Brown, Norman Oliver, 1913-2002 (Wesleyan University Press ; Distributed by Harper & Row, 1985)
Product Description: A shocking and extreme interpretation of the father of psychoanalysis.
Keywords: Civilization -- Philosophy.; Civilization -- Psychological aspects.; Psychohistory.; Psychoanalysis.; Death instinct.; Civilisation -- Philosophie.; Civilisation -- Aspect psychologique.; Psychohistoire.; Psychanalyse.; Pulsion de mort.; psychohistory.; psychoanalysis.; PSYCHOLOGY -- Movements -- Psychoanalysis.; Civilization -- Philosophy; Civilization -- Psychological aspects; Death instinct; Psychoanalysis; Psychohistory; Cultuurfilosofie.; Seksualiteit.